Effect of Supervision on Employee Performance in Business Organisations in Kabale District: A Case Study of Kigezi Industries Limited in Kabale Municipality. - Natiimba, Shiphra (Kabale University, 2024)
This study examined the effect of supervision on employee performance in business organizations in Kabale district a case study of Kigezi Industries Limited in Kabale Municipality. The objectives of the study were; to examine different techniques of supervision used in business organizations to enhance employee performance, to investigate the effect of supervision on employee performance in business organizations, and to identify other related factors that affect employee performance apart from supervision of employees in business organizations. A descriptive research design was used and data was collected using interviews and questionnaires. The study findings on the different techniques of supervision used in business organizations to enhance employee performance were; employee training and development, peer review and team evaluation, performance appraisals, coaching and mentoring, and behavior-based feedback. The study findings on the effects of supervision on employee performance in business organizations were; job satisfaction, motivation and engagement, team collaboration, feedback and improvement, and reduced turnover of employees. The study findings on the other related factors that affect employee performance apart from supervision of employees in business organizations were; work environment, recognition and rewards, company culture, leadership, and job security. The study recommended that organizations should provide employee assistance programs that offer support for personal and professional challenges which can include counseling services, financial advice, or other resources to help employees navigate difficulties and improve their performance and the supervisors of the organizations should ensure that training programs that are given to employees align with the overall goals and objectives of the organization since this alignment can help employees to understand the relevance of their training to the success of the company.